Impact of capital markets in the economic growth of Zimbabwe (1990-2022) - Togarepi, Gabriel (BUSE, 2024)
Gross Domestic Product (GDP), highlighting the complexities and interdependencies between financial systems and economic growth. A declining capital market often signals investor uncertainty, reduced capital allocation, and diminished economic activity, which can exacerbate stagnation in GDP growth. The analysis identifies key factors contributing to this adverse relationship, including regulatory inefficiencies, market volatility, and investor confidence. We discuss various policy responses aimed at mitigating these negative effects, such as enhancing regulatory frameworks, implementing monetary policy adjustments, and fostering fiscal stimulus. Additionally, the paper emphasizes the importance of structural reforms to promote innovation and entrepreneurship, which can rejuvenate both capital markets and economic performance. Ultimately, understanding the dynamics of this relationship is crucial for policymakers to formulate effective strategies that align capital market health with sustainable economic growth.
Keywords: Capital markets; Economic growth; Zimbabwe; Gross Domestic Product